LEVEL SELECTION OF NON-TRAUMATIC LOWER EXTREMITY AMPUTATIONS IN PATIENTS WITH CRITICAL ISCHEMIA - S.M. Vasyliuk; V.S. Osadets; O.V. Prudnikov; O.M. Makarchuk; B.V. Krysa; V.V. Ivanyna (Сучасні медичні технології)
Objective. To evaluate the informativeness of ultrasound scanning of the lower limb arteries and angiography in patients with critical ischemia for choosing the optimal level of extremity amputation.